When object clitisation and climbing happen alone, and when they dance cheek to cheek: Selective impairment in Spanish agrammatism (2013)
Previous studies have shown that production of clitics in agrammatic Broca’s aphasia is compromised, either by analyzing spontaneous speech (Nespoulous et al., 1988; Reznik et al.,1995; Stavrakaki and Kouvava, 2003; Chinellato, 2004; Rossi, 2007) or by testing clitic production in an experimental setting (Rossi, 2007; Gavarró, 2008, Nerantzini, 2008; Martínez-Ferreiro, 2010). Clitics in agrammatism have only been explored in Greek, Italian, French and Ibero-Romance (Spanish, Catalan and Galician). In Spanish, the study reported by Reznik et al. (1995) explicitly focused on the production of clitics in aphasic spontaneous speech, while Martínez-Ferreiro (2010) tested clitic production and comprehension in an experimental setting. This study focuses on the morpho-syntactic problems of Spanish agrammatic speakers with emphasis on the production of sentence Word order. Because of the particular flexible word order with which Spanish can be grammatically produced, and due to the predictions that can be drawn from the ‘Derived Order Problem Hypothesis’ (DOP-H) (Bastiaanse & van Zonneveld, 2005), the present study focuses on two movement operations, clitic and object scrambling, in a way that has not been explored before. It is hypothesized that syntactic complexity, in a linguistic sense, is a critical factor in agrammatic production, and, therefore, it is predicted that sentences with object movement and clitic movement will be more difficult than sentences with basic word order (SVO), regardless of the position in the syntactic tree.